The Implementation of Australia’s “Stepping-Up Engagement” with the Melanesian States as the Defence Strategy of Australia to Respond to the Rise of China in the South Pacific Region (2013-2018) - Anak Agung Banyu Perwita (Department of International Relations, Universitas Andalas, 2020)
The rise of China in the South Pacific region indicates China’s growing political-diplomatic, economic, and the possibility of military presence within the region. Accordingly, it develops Australia’s threat perception and affects Australia’s national interest. A secure nearer region is the second most important in Australia’s strategic defense interests. Therefore, the stability and security of the South Pacific region are crucial to Australia’s national interests. This research discussed Australia’s “Stepping-Up engagement” as the defense strategy of Australia to strengthen its bilateral defense relations with the Melanesian states as the response to the rise of China. In addition, the research is constructed by using the concept of national interest, threat perception, defence strategy and bilateral defence relations through qualitative research method. This research explains the implementation of Australia’s “Stepping-Up engagement” with the Melanesian states as the defence strategy of Australia to respond to the rise of China in the South Pacific region.